Trapped: High Inequality and Low Growth in Latin America and the Caribbean - United Nations Development Programme (United Nations, 2023)
Latin America and the Caribbean is a region of great contrasts, where wealth and prosperity coexist with vulnerability and extreme poverty. The list of contrasts is long and familiar. The region is also characterized by very volatile and low average growth, explained by low productivity. This Regional Human Development Report argues that the region is caught in a double trap of high inequality and low growth. These two phenomena interact in a vicious circle that limits the ability to advance on all fronts of human development. Understanding the nature of the trap is critical to breaking free from it.